2014
DOI: 10.1002/ijc.29117
|View full text |Cite
|
Sign up to set email alerts
|

Two major pathways of recurrent high‐grade squamous intraepithelial lesions of the cervix

Abstract: Dear Sir,We read with interest the article by Herfs et al. 1 reporting the outcome of 131 consecutive patients with SIL after electrosurgical excision procedure (LEEP) during a mean follow-up period of 1.7 (0.4-3.5) years. About 94.3% of patients had high-grade squamous intraepithelial lesions (HSIL) at time of primary treatment. In four patients with positive resection margins in their initial cone specimen, HSIL was detected after 3 months and interpreted as persistent disease. Both primary and persistent le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…6 The comparable SOX17 expression patterns in reserve cells and in the remnants of IMM support the general opinion that reserve cells are the progenitors for IMM and may therefore provide additional evidence for the reserve cell as the progenitor of cervical (pre)neoplasia. 13,22,43,45 The reserve cells, in turn, are suggested to originate from either the basal cells of the squamous epithelium 14,46 or from the stretch of cuboidal cells at the SqCJ recognized by Herfs et al 15 Although we did not specifically recognize these stretches of cuboidal cells in our tissue samples, it is very likely that these latter cells are also SOX17 positive.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…6 The comparable SOX17 expression patterns in reserve cells and in the remnants of IMM support the general opinion that reserve cells are the progenitors for IMM and may therefore provide additional evidence for the reserve cell as the progenitor of cervical (pre)neoplasia. 13,22,43,45 The reserve cells, in turn, are suggested to originate from either the basal cells of the squamous epithelium 14,46 or from the stretch of cuboidal cells at the SqCJ recognized by Herfs et al 15 Although we did not specifically recognize these stretches of cuboidal cells in our tissue samples, it is very likely that these latter cells are also SOX17 positive.…”
Section: Discussionmentioning
confidence: 65%
“…5,16,26,41 The debate about the cells of origin for these lesions is, however, still ongoing. 15,16,42,43 Neoplasia in the cervix is suggested to occur at particular epithelial sites, where vulnerable cells, such as the reserve cells or cuboidal cells, are found. 14,15 The underlying study focuses on SOX2 and SOX17 expression during (pre)neoplastic transformation of the uterine cervix.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…
The authors list two criticisms in their letter. 1 The first is that the follow-up period in this study was not long enough to appreciate potential new infections that could result in high grade cervical intraepithelial neoplasia (CIN) despite the presumed excision of the squamocolumnar (SC) junction. The second is that reserve cells are important progenitors of preinvasive squamous lesions of the cervix and because of their wider distribution they cannot be excised surgically.Concerning the first criticism, the authors describe studies from their institution that reported a recurrent CIN3 or adenocarcinoma in situ in less than 4 women per 1,000 treated by excision for CIN3 with negative margins, in contrast to 22% of those with positive margins.
…”
mentioning
confidence: 99%
“…The authors list two criticisms in their letter. 1 The first is that the follow-up period in this study was not long enough to appreciate potential new infections that could result in high grade cervical intraepithelial neoplasia (CIN) despite the presumed excision of the squamocolumnar (SC) junction. The second is that reserve cells are important progenitors of preinvasive squamous lesions of the cervix and because of their wider distribution they cannot be excised surgically.…”
mentioning
confidence: 99%